DETERMINATION OF FUNCTIONAL GROUPS OF TREE SPECIES IN AN INSULAR ENVIRONMENT - Brodbeck, Bruna; Melo Júnior, João Carlos Ferreira (Floresta, 2024)
The Atlantic Forest is the third largest biome in Brazil, but currently, approximately 12.4% of its native vegetation remains. Given its importance and structural complexity, studies that contribute to its conservation appeal have been increasingly requested. In this context, the functional approach has helped improve the understanding of the coexistence patterns of tree species in forest communities. This separation of species into functional groups aims to highlight the functioning of one or more processes of interest. The present study aimed to identify the functional groups, richness, and diversity of the vegetation of Ilha dos Remédios, located in the municipality of Balneário Barra do Sul/SC. The island has an area of approximately 246,013 m² and is 1.5 km from the mainland. To identify the arboreal vegetation, sampling was conducted using the 100 m² plot method. A total of 244 individuals were sampled, belonging to 26 species from 18 families, divided into 3 functional groups through Cluster Analysis. A low diversity of functional groups was recorded, with an overlap of these groups in some ecological attributes, corroborating the trend towards functional redundancy in historically degraded areas such as the study area.